The routine collection of patient-reported outcome measures (PROMs) for long-term conditions in primary care: a cohort survey. Issue 2 (21st February 2014) - Peters, Michele; Crocker, Helen; Jenkinson, Crispin; Doll, Helen; Fitzpatrick, Ray
Abstract : Objectives: To evaluate the feasibility of using patient-reported outcome measures (PROMs) for long-term conditions (LTCs) in primary care. Design: A cohort postal survey conducted from September 2010 to April 2012. Setting: Primary care practices (n=33) in London and the North-West of England. Participants: 4484 patients with a diagnosis of asthma, chronic obstructive pulmonary disease, diabetes, epilepsy, heart failure or stroke were sent a survey at baseline. Main outcome: The main outcome was to evaluate the feasibility of and the recruitment strategies for collecting PROMs data in LTCs by assessing the response rates for the baseline and follow-up surveys. Secondary outcomes were the evaluation of change scores of the EQ-5D index and visual analogue scale (VAS) between baseline and follow-up surveys. Results: The baseline survey achieved a response rate of 38.4% (n=1721/4485) and at follow-up 71.5% (n=1136/1589). Response rates varied by LTC. Little change was found in health-related quality of life for the total sample (−0.001 for the EQ-5D index score and 0.12 for the EQ-5D VAS) between patients responding to both the baseline and follow-up surveys. Conclusions: The response rate to the baseline survey was similar to that of other general practice surveys. Current UK policy aims to assess health service performance in LTCs by means of using PROMs. It thus would be desirable to improve response rates by making the invitation to self-reports of health-related quality of life more engaging for patients. Results on the EQ-5D score raise questions about optimal indicators for LTCs and appropriate timelines for assessment.